2023
DOI: 10.1111/ene.15692
|View full text |Cite
|
Sign up to set email alerts
|

White matter hyperintensity burden predicts cognitive but not motor decline in Parkinson's disease: results from the Ontario Neurodegenerative Diseases Research Initiative

Abstract: White matter hyperintensity burden predicts cognitive but not motor decline inParkinson's disease. Results from the ONDRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
0
6
0
1
Order By: Relevance
“…According to previous literature, PD patients exhibited widespread impairment of white matter integrity 37,40 and white matter degeneration was associated with faster progressive parkinsonism in PD 41 . In addition, white matter hyperintensity burden was a reliable predictor of cognitive decline in PD patients 42–44 . Therefore, aging may shape the progression of motor and non‐motor symptoms in PD by inducing white matter damages 37 .…”
Section: Discussionmentioning
confidence: 94%
“…According to previous literature, PD patients exhibited widespread impairment of white matter integrity 37,40 and white matter degeneration was associated with faster progressive parkinsonism in PD 41 . In addition, white matter hyperintensity burden was a reliable predictor of cognitive decline in PD patients 42–44 . Therefore, aging may shape the progression of motor and non‐motor symptoms in PD by inducing white matter damages 37 .…”
Section: Discussionmentioning
confidence: 94%
“…For structural network, PD patients display extensive disruptions of white matter integrity [17], which is associated with worse disease severity and cognitive decline [18, 19]. Particularly, the burden of white matter hyperintensity has been demonstrated to be an imaging biomarker of cognitive impairment in PD patients [20]. Therefore, white matter disruptions have been considered as an essential culprit for cognitive decline in PD patients.…”
Section: Introductionmentioning
confidence: 99%
“…According to previous literature, PD patients exhibited extensive impairment of white matter integrity [92, 93], which was associated with faster disease progression in PD [94]. Additionally, the burden of white matter hyperintensity was a powerful predictor of cognitive decline in PD patients [9597]. In a recent study, we revealed age-associated changes in white matter network metrics were causally associated with cognitive assessments of PD patients [25].…”
Section: Discussionmentioning
confidence: 83%